2018
DOI: 10.1589/jpts.30.185
|View full text |Cite
|
Sign up to set email alerts
|

Relief of exertional dyspnea and spinal pains by increasing the thoracic kyphosis in straight back syndrome (thoracic hypo-kyphosis) using CBP<sup>®</sup> methods: a case report with long-term follow-up

Abstract: [Purpose] To present the clinically significant improvement of straight back syndrome (SBS) in a patient with spinal pain and exertional dyspnea. [Subject and Methods] A 19 year old presented with excessive thoracic hypokyphosis and other postural deviations. A multimodal CBP® mirror image® protocol of corrective exercises, traction procedures and spine/posture adjusting were given over an initial 12-week course of intensive treatment followed by a 2.75 year follow-up with minimal supportive treatment. [Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 35 publications
(58 reference statements)
1
22
0
Order By: Relevance
“…Recent advances in manual therapy traction methods by the Chiropractic BioPhysics ® (CBP ® ) group have shown that non-surgical rehabilitation of the lumbar lordosis is possible; for example, as presented in several case reports 17 , 18 , 19 , 20 ) . CBP methods is a full-spine and posture correcting technique (www.idealspine.com); however, for the purposes of this review we will focus on its employment of the unique ‘extension traction’ targeted to the lumbar spine in patients presenting with lumbar spine hypolordosis with various low back disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in manual therapy traction methods by the Chiropractic BioPhysics ® (CBP ® ) group have shown that non-surgical rehabilitation of the lumbar lordosis is possible; for example, as presented in several case reports 17 , 18 , 19 , 20 ) . CBP methods is a full-spine and posture correcting technique (www.idealspine.com); however, for the purposes of this review we will focus on its employment of the unique ‘extension traction’ targeted to the lumbar spine in patients presenting with lumbar spine hypolordosis with various low back disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This is the second case documenting the increase in thoracic hypokyphosis in a patient with SBS and related symptoms by CBP ® methods. In the case by Betz et al 9 ) , 37 treatments were performed over 12-weeks, resulting in a 14° improvement. That is very similar to this case, a 10° improvement in 36 treatments over 16-weeks.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of data on the effectiveness of increasing the thoracic kyphosis by nonsurgical means; we could only locate two cases detailing the treatment of SBS patients in the literature 8 , 9 ) . The first was an adult female patient with scoliosis; over a 4 year period the patient had a 16° improvement in thoracic kyphosis after receiving a variety of treatments including deep tissue massage, outpatient psychological therapy, daily exercise focusing on mobilization of the chest wall, and manipulation 8 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common X-ray is an essential tool for doctors and manual therapists in the treatment of musculoskeletal and neuromusculoskeletal diseases and conditions associated with poor posture and spinal deformity. 1 10 There has been an ever-expanding evidence base substantiating the effectiveness of nonsurgical rehabilitative methods for the treatment of posture and spinal deformities, such as forward head posture, 11 20 cervical hypolordosis/kyphosis, 14 21 thoracic hyperkyphosis, 22 29 thoracic hypokyphosis, 30 , 31 lumbar hypolordosis/kyphosis, 32 37 and scoliosis. 38 41 …”
Section: Introductionmentioning
confidence: 99%